ANALISIS NILAI KEARIFAN LOKAL SATUA MANIK ANGKERAN DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA BALI - I Wayan Sujana; Ida Bagus Yoga Swadnyana; Ni Kadek Ayu Sri Utami; Ni Made Dwi Merta Septiari; I Gusti Ayu Diantari; Ni Kadek Riska Dewi (STKIP Subang, 2026)
Satua is one of the forms of Balinese oral literature that is rich in local wisdom values and has become an inseparable part of Balinese cultural life since ancient times. One of the most well-known and meaningful satua is the satua of Manik Angkeran, which embodies the philosophy of Tri Hita Karana as the foundation of Balinese society. This study aims to analyze the local wisdom values contained in the satua of Manik Angkeran and their relevance in Balinese language learning at the elementary and secondary school levels. The study employs a qualitative approach using content analysis and library research methods through textual examination of the satua, literature review, and analysis of Balinese language curriculum documents. The results indicate that the satua of Manik Angkeran contains four local wisdom values, namely: (1) religious values reflected in the concepts of karma phala and dharma; (2) moral values in the form of obedience, responsibility, and atonement; (3) socio-cultural values in the form of respect for parents and ancestors; and (4) ecological values in the form of appreciation for nature and living beings. These values are relevant to be integrated in Balinese language learning and have the potential to serve as a foundation for character education based on local wisdom for Balinese students.